Phase locking of nanosecond Gunn-effect oscillators; Instruments and Experimental Techniques; Vol. 54, iss. 6 - Konev V. Yu. Vladimir Yurievich; Gubanov V. P. Vladimir Petrovich; Klimov A. I. Aleksey Ivanovich; Koval’chuk O. B. Oleg Borisovich; Rostov V. V. Vladislav Vladimirovich; Yalandin M. I. Michael Ivanovich (2011, 2011)
Title screen